Tropical plants do not have narrower temperature tolerances, but are more at risk from warming because they are close to their upper thermal limits - Alexander T. Sentinella; David I. Warton; William B. Sherwin; Catherine A. Offord; Angela T. Moles (Global Ecology and Biogeography, 2020)
Aim Tropical species are thought to be more susceptible to climate warming than are higher latitude species. This prediction is largely based on the assumption that tropical species can tolerate a narrower range of temperatures. While this prediction holds for some animal taxa, we do not yet know the latitudinal trends in temperature tolerance for plants. We aim to address this knowledge gap and establish if there is a global trend in plant warming risk. Location Global. Time period Present–2070. Major taxa studied Plants. Methods We used 9,737 records for 1,312 species from the Kew Gardens’ global germination database to quantify global patterns in germination temperature. Results We found no evidence for a latitudinal gradient in the breadth of temperatures at which plant species can germinate. However, tropical plants are predicted to face the greatest risk from climate warming, because they experience temperatures closer to their upper germination limits. By 2070, over half (79/142) of tropical plant species are predicted to experience temperatures exceeding their optimum germination temperatures, with some even exceeding their maximum germination temperature (41/190). Conversely, 95% of species at latitudes above 45° are predicted to benefit from warming, with environmental temperatures shifting closer to the species’ optimal germination temperatures. Main conclusions The prediction that tropical plant species would be most at risk under future climate warming was supported by our data, but through a different mechanism to that generally assumed.